ISOLATION OF PROBIOTIC BACTERIA FROM CTERIA FROM CTERIA FROM Panchamirtham: ETHINIC SOUTHERN INDIAN FERMENTED FRUIT MIX - S. UMA MAHESHWARI,; S. AMUTHA,; G. HEMALATHA,; N. SENTHIL,; R. ANANDHAM,; K. KUMUTHA, (The Bioscan, 2019)
Probiotics are beneficial microbes that confer a realistic health benefit on the host, which in combination with prebiotics, (indigestible dietary fibre/carbohydrate), increases health benefit. Hence, the present study was directed towards the isolation of probiotic bacteria from Panchamirtham which is fermented fruit mix. A total of three samples of Panchamirtham were collected from three different locations for the isolation of probiotic bacteria by using MRS agar medium. Fifteen isolates were selected based on colour, size and shape. Isolates were tested for pH and sucrose tolerance. The 58 and 61% of the isolates tolerated pH 5 and 8 respectively. Among the bacterial isolates, five percent, seventy percent, seventy five percent and eighty percent showed 100, 80, 67 and 47% sucrose tolerance, respectively. Among the isolated bacteria, ninety three percent were Gram positive which exhibited negative for catalase, citrate, H2S and gelatin hydrolysis. Based on the biochemical and morphological tests isolated bacteria were tentatively identified as Lacococcus spp.,